Property Tax Competition: A Quantitative Assessment - Rainald Borck; Jun Oshiro; Yasuhiro Sato (Center for Economic Studies and ifo Institute (CESifo), 2022)
We develop a model of property taxation and characterize equilibria under three alternative taxation regimes often used in the public finance literature: decentralized taxation, centralized taxation, and "rent seeking" regimes. We show that decentralized taxation results in inefficiently high tax rates, whereas centralized taxation yields a common optimal tax rate, and tax rates in the rent-seeking regime can be either inefficiently high or low. We quantify the effects of switching from the observed tax system to the three regimes for Japan and Germany. The decentralized or rent-seeking regime best describes the Japanese tax system, whereas the centralized regime does so for Germany. We also quantify the welfare effects of regime changes.
Keywords: H71; H72; R13; R51; 330; property taxes; tax competition; efficiency